2003
DOI: 10.22621/cfn.v117i4.825
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Habitat Use and Movements of Mountain Goats, <em>Oreamnos americanus</em>, in East-central British Columbia

Abstract: Poole, Kim G., and Douglas C. Heard. 2003. Seasonal habitat use and movements of Mountain Goats, Oreamnos americanus, in east-central British Columbia. Canadian Field-Naturalist 117(4): 565-576.To identify the potential for adverse effects of forest development on Mountain Goats (Oreamnos americanus), we documented the patterns of forest use by goats and the factors influencing goat habitat use. We used a combination of 15 very high frequency (VHF) and six global positioning system (GPS) radiocollars to docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 15 publications
(22 reference statements)
5
33
0
Order By: Relevance
“…During winter, mountain goats also tend to use areas with low cumulative snow depths often characterized by rocky windswept outcrops and ledges found in steep rugged terrain (Hebert and Turnbull 1977;Côté and Festa-Bianchet 2003;Poole et al 2009). Association with escape terrain is stronger during winter (Poole and Heard 2003;White 2006), but little is known about the effect of snow on this association. During winter, darkness may last for 15 h a day.…”
Section: Introductionmentioning
confidence: 99%
“…During winter, mountain goats also tend to use areas with low cumulative snow depths often characterized by rocky windswept outcrops and ledges found in steep rugged terrain (Hebert and Turnbull 1977;Côté and Festa-Bianchet 2003;Poole et al 2009). Association with escape terrain is stronger during winter (Poole and Heard 2003;White 2006), but little is known about the effect of snow on this association. During winter, darkness may last for 15 h a day.…”
Section: Introductionmentioning
confidence: 99%
“…Janeau et al (2004) reported a success fix rate of 92.5% (39.1% 2D and 53.4% 3D) with red deer in deciduous forest in the leaf-off period (NovemberÁApril) and 86.5% (48.5% 2D and 38.04% 3D) in the leaf-on period (MayÁOctober). Poole and Heard (2003) reported a 76% success fix rate (15% 2D and 61% 3D) for mountain goats in mountainous terrain. Graves and Waller (2006) had a 72% success fix rate tracking bears in coniferous forest in mountainous terrain, even though the attempt-fix length of 3 min was considerably longer than the attempt-fix length of 70 s used in the present study.…”
Section: Gps Fixesmentioning
confidence: 99%
“…Overall, the success fix rate was 91.7%, with 27.5% 2D fixes and 64.2% 3D fixes. The majority of previous studies involving GPS collars do not report fix interval, success fix rate or fix type (Cain et al 2005), and those studies that did used either stationary collars, which have a higher success rate than collars deployed on animals ), or collars deployed on wildlife (Poole and Heard 2003;Pepin et al 2004). Few reports concerning use of GPS collars on livestock included a success fix rate or fix type.…”
Section: Gps Fixesmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of studies have documented geophagic behavior within this species, highlighting either individual movement patterns to specific lick sites or the nutrient composition of preferred licks (Jones and Hanson 1985;Poole and Heard 2003;Poole et al 2010;Rice 2010) or discussed its potential role in home-range limitations (Hebert 1965;Festa-Bianchet 1988). We aimed to understand what specific nutrients goats were seeking at lick sites.…”
Section: Introductionmentioning
confidence: 99%